Kinerja Akuisisi Industri Semen di Indonesia Tahun 2009 – 2013 [The Performance of Cement Industry Acquisitions in Indonesia 2009 – 2013] - Imelda Imelda; Rina Adi Kristianti (DeReMa (Development Research of Management): Jurnal Manajemen, 2017)
This research tried to explore the long term financial performance (window period = 3 years) after aquisitions in the cement industry during the period 2009–2013. The dependent variable is the period of three years before and after the acquisitions and the independent variables are current ratio, return on asset, debt to equity ratio, total asset turnover, net profit margin and stock return. Sampling technique is purposive sampling and the samples obtained amounted to 18 companies. Data processing techniques using different test by comparing the financial performance before and after the acquisition for a long period of 3 years. The results show there are significant differences in debt to equity ratio, net profit margin and stock returns. The cement industry has high debt, negative profit and positive stock return after three years of acquisition. This shows that although the industry has high debt, profit is still negative but responded positively by the market. Bahasa Indonesia Abstrak: Penelitian ini mencoba mengeksplorasi kinerja keuangan jangka panjang setelah merger (windows period = 3 tahun) pada industri semen tahun 2009 – 2013. Variabel dependen adalah periode tiga tahun sebelum dan setelah akuisisi dan varaibel independen adalah current ratio, return on asset, debt to equity ratio, total asset turnover, net profit margin dan return saham. Teknik pengambilan sampel adalah purposive sampling dan sampel yang diperoleh berjumlah 18 perusahaan. Teknik pengolahan data menggunakan uji beda dengan membandingkan kinerja keuangan sebelum dan setelah akuisisi untuk periode jangka panjang yaitu 3 tahun. Hasilnya  menunjukkan ada perbedaan signifikan debt to equity ratio, net profit margin dan return saham.  Industri semen memiliki hutang tinggi, profit negative dan return saham positif setelah tiga tahun akuisisi. Hal ini menunjukkan bahwa walaupun industri ini memiliki hutang tinggi, profit masih negative tetapi direspon positif oleh pasar.